2021
DOI: 10.1016/s1473-3099(20)30843-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and immunogenicity of an inactivated SARS-CoV-2 vaccine in healthy adults aged 18–59 years: a randomised, double-blind, placebo-controlled, phase 1/2 clinical trial

Abstract: Background With the unprecedented morbidity and mortality associated with the COVID-19 pandemic, a vaccine against COVID-19 is urgently needed. We investigated CoronaVac (Sinovac Life Sciences, Beijing, China), an inactivated vaccine candidate against COVID-19, containing inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), for its safety, tolerability and immunogenicity. Methods In this randomised, double-blind, placebo-controlled, phase 1/2 clinical trial, healthy adults aged 18-59 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

82
1,337
11
51

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,327 publications
(1,481 citation statements)
references
References 23 publications
82
1,337
11
51
Order By: Relevance
“…Furthermore, they protected NHPs against challenge by SARS-CoV-2, suggesting an important role for humoral responses as the immune correlates of protection. Initial clinical trial studies of these two inactivated vaccine candidates showed that, similar to in NHPs, these vaccines elicited substantial nAbs in humans 145,146 . These inactivated vaccine candidates did not induce either T H 1 or T H 2 cell-associated cytokines in those vaccinated.…”
Section: E and N Proteinsmentioning
confidence: 99%
“…Furthermore, they protected NHPs against challenge by SARS-CoV-2, suggesting an important role for humoral responses as the immune correlates of protection. Initial clinical trial studies of these two inactivated vaccine candidates showed that, similar to in NHPs, these vaccines elicited substantial nAbs in humans 145,146 . These inactivated vaccine candidates did not induce either T H 1 or T H 2 cell-associated cytokines in those vaccinated.…”
Section: E and N Proteinsmentioning
confidence: 99%
“…Results from measles virus and vesicular stomatitis virus (VSV) based vaccine candidates in animal models were also reported (Horner et al, 2020;. Three studies reported preliminary results on the safety and immunogenicity of inactivated COVID-19 vaccines from phase I/II clinical trials (Che et al, 2020;Zhang et al, 2020g). The inactivated vaccines demonstrated acceptable safety profiles and were effective in inducing neutralizing antibodies.…”
Section: Progress Of Covid-19 Vaccine Developmentmentioning
confidence: 99%
“…The participant remained in the study and did not report a similar reaction after the booster dose. Overall, there was no significant difference in AEs among study groups [ 237 ].…”
Section: Sars-cov-2 Vaccine Candidates In Phase III Clinical Trialsmentioning
confidence: 99%
“…Higher nAb and binding IgG titers in the Phase II trial (compared to Phase I) was due to a different vaccine production process for the Phase II study which inadvertently increased the content of spike protein in the vaccine used for Phase II studies by almost two-fold. T cell responses were determined by measuring IFN-γ in an ELISpot assay wherein PBMCs were cultured with overlapping peptides from the S protein or controls peptides [ 237 ].…”
Section: Sars-cov-2 Vaccine Candidates In Phase III Clinical Trialsmentioning
confidence: 99%